2010
DOI: 10.1029/2010gl044548
|View full text |Cite
|
Sign up to set email alerts
|

Potential climate impact of black carbon emitted by rockets

Abstract: A new type of hydrocarbon rocket engine is expected to power a fleet of suborbital rockets for commercial and scientific purposes in coming decades. A global climate model predicts that emissions from a fleet of 1000 launches per year of suborbital rockets would create a persistent layer of black carbon particles in the northern stratosphere that could cause potentially significant changes in the global atmospheric circulation and distributions of ozone and temperature. Tropical stratospheric ozone abundances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 28 publications
9
68
1
1
Order By: Relevance
“…The factor of 2/3 accounts for typical launches where about two thirds of a rocket's total propellant burn (all stages, to orbit) takes place above the tropopause. Previous global models [Jackman et al, 1998;Danilin et al, 2001;Ross et al, 2010] suggest that midlatitude launches generate a zonally symmetric accumulation region between about 15 and 30 km altitude and 30 ∘ N-80 ∘ N latitude, illustrated in Figure 2. Equatorial launch emissions (accounting for ∼20% of all launches) will be entrained in the vertical flow at low latitudes and will possibly add proportionally less to the accumulation region than the midlatitude launches.…”
Section: Emission Indices and Stratospheric Burdenmentioning
confidence: 99%
See 4 more Smart Citations
“…The factor of 2/3 accounts for typical launches where about two thirds of a rocket's total propellant burn (all stages, to orbit) takes place above the tropopause. Previous global models [Jackman et al, 1998;Danilin et al, 2001;Ross et al, 2010] suggest that midlatitude launches generate a zonally symmetric accumulation region between about 15 and 30 km altitude and 30 ∘ N-80 ∘ N latitude, illustrated in Figure 2. Equatorial launch emissions (accounting for ∼20% of all launches) will be entrained in the vertical flow at low latitudes and will possibly add proportionally less to the accumulation region than the midlatitude launches.…”
Section: Emission Indices and Stratospheric Burdenmentioning
confidence: 99%
“…We do not consider atmospheric features that evolve in response to the change in radiative flux in the accumulation layer, which may be significant, essentially restating that we use instantaneous RF in order to keep that point clear. Ross et al [2010] showed how modest localized BC heating in the rocket accumulation layer can modify the global circulation; changes in the global ozone distribution were significant in that work as the atmosphere returned to thermal equilibrium.…”
Section: Ross and Sheaffermentioning
confidence: 99%
See 3 more Smart Citations